(untitled) (Journal of the Digital Humanities Association of Southern Africa (DHASA), 2023)
This paper deals with an electronic resource under construction. The objective is to construct a lexical database of Malagasy adjectives. Malagasy is an agglutinative language of Austronesian origin, spoken in the African island of Madagascar. The method used to construct the resource is adapted from the approach of Gross (1989) to electronic dictionaries. The content of the resource is based on linguistic analysis and encoded so as to be used by language-processing software. However, care has been taken that all linguistic information is easily readable and updatable. The resource allows for morphological analysis and generation of adjectives, removing obstacles to the construction of computer applications to process the Malagasy language. The originality of this paper also comes from our proposal of a distinction between adjectives in the usual sense and adjectival forms of other parts of speech.